2022
DOI: 10.1002/cncr.34209
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based stress reduction and cognitive function among breast cancer survivors: A randomized controlled trial

Abstract: BACKGROUND: Breast cancer (BC) survivors frequently report changes in cognition after chemotherapy. Mindfulness may benefit survivors by mitigating cancer-related cognitive impairment. As part of a larger study investigating the effects of mindfulness-based stress reduction (MBSR) for BC survivors living with neuropathic pain, the authors assessed whether MBSR would have an effect on cognitive outcomes. METHODS: Participants were randomized to an MBSR intervention group (n = 30) or a waitlist control group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Improvement was seen in language skills measured by Delis‐Kaplan Executive Function System (DKEFS) ( p < 0.05), executive function measured by the Dysexecutive Questionnaire (DEX) ( p < 0.05) and cognitive failures measured by the CFQ ( p < 0.05). One study 64 included an element of mindfulness‐based stress reduction in addition to CBT and found no statistically significant improvement in cognitive function. Lin et al 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Improvement was seen in language skills measured by Delis‐Kaplan Executive Function System (DKEFS) ( p < 0.05), executive function measured by the Dysexecutive Questionnaire (DEX) ( p < 0.05) and cognitive failures measured by the CFQ ( p < 0.05). One study 64 included an element of mindfulness‐based stress reduction in addition to CBT and found no statistically significant improvement in cognitive function. Lin et al 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent research showed that a mindfulness-based stress reduction approach, group counseling, and survivorship education could reduce depressive symptoms in young breast cancer survivors ( Mirmahmoodi et al, 2020 ; Bower et al, 2021 ; Printz, 2021 ). Mindfulness has also benefited survivors by eliminating cancer-related pain and cognitive impairment ( Smith et al, 2021 ; Duval et al, 2022 ). It was proven that implementing the multi-modal mindfulness-based intervention, including integrative dietary, physical activity, and mindfulness, enhanced breast cancer survivors’ quality of life and healthy lifestyle ( Ruiz-Vozmediano et al, 2020 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our exploratory neuroimaging studies investigating the influence of mindfulness on brain resting state and white matter integrity as well as emotional reactivity among 21 participants found a potential impact of MBSR on the neural correlates of CNP due to breast cancer treatment. These included improved white matter integrity in several brain regions [ 23 ], reduced activation in several brain areas involved in pain processing and emotional processing in the presence of pain-related stimuli (emotional Stroop task) [ 22 ], as well as altered default mode network activity/connectivity post-MBSR in comparison to controls [ 21 ]. The effect of natural recovery from cancer treatment-induced chronic neuropathic pain may have masked any effect of MBSR in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Our secondary hypotheses were that participation in MBSR would result in reduced psychological distress and pain-related cognition, and improved quality of life at 3-month follow-up relative to control. Three exploratory studies focusing on the effects of MBSR training on cognitive function [ 21 ], brain structure [ 22 ] and function [ 23 ], and biomarkers of stress and inflammation [ 24 ] are reported in detail in separate manuscripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation